2002
DOI: 10.1002/mpo.10092
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex RT‐PCR assay for the detection of major fusion transcripts in Taiwanese children with B‐lineage acute lymphoblastic leukemia

Abstract: Multiplex RT-PCR assay is an efficient, sensitive, accurate, and cost-effective diagnostic tool, which will likely improve our ability in accurately and rapidly risk-stratifying children with ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…Taken together, the frequency of Ras mutations in the current series was 20.8% in children with B-precursor ALL, which comprised of 86% of patients with childhood ALL in Taiwan. 26 Lü bbert et al reported that 6 of 100 children (6%) with ALL carried N-Ras mutations, 15 but none had K-Ras mutations. Yokota et al observed that 14 of 125 Japanese children (11%) with ALL had N-Ras mutations that were not correlated with outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the frequency of Ras mutations in the current series was 20.8% in children with B-precursor ALL, which comprised of 86% of patients with childhood ALL in Taiwan. 26 Lü bbert et al reported that 6 of 100 children (6%) with ALL carried N-Ras mutations, 15 but none had K-Ras mutations. Yokota et al observed that 14 of 125 Japanese children (11%) with ALL had N-Ras mutations that were not correlated with outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Leukemic cells were classified as B-lineage or T-lineage and further by cytogenetic evaluation and/or molecular analysis, performed as described earlier. 4 All protocols were approved by the Institutional Review Boards of the participating institutions. Written informed consent was obtained for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the frequency of ETV6-RUNX1 fusion in Taiwan, 18-19% in B-lineage ALL, has been consistently lower than that (B25%) in western countries. 4,22 In Japan, the frequency of ETV6-RUNX1 fusion in children with ALL seems to be even lower than in Taiwan (13%). 23 The frequency of hyperdiploidy with a modal chromosome number of 51-68 is also lower (11.9%) in childhood ALL cases in Taiwan than in western countries (25-27%).…”
Section: -Year Efs (%)mentioning
confidence: 99%
“…The mononuclear cells were isolated from bone marrow samples and cryopreserved until use. Standard morphological classification, immunophenotyping, and cytogenetic analysis were performed at initial diagnosis as described previously [8]. CNS leukemia was defined as the presence of leukemic cells on a cytocentrifuged preparation of cerebrospinal fluid in conjunction with ≥5 WBC/L.…”
Section: Patients and Samplesmentioning
confidence: 99%